Outcomes of a randomized quality improvement trial for high‐risk Veterans in year two. (18th June 2021) - Chang, Evelyn T.; Yoon, Jean; Esmaeili, Aryan; Zulman, Donna M.; Ong, Michael K.; Stockdale, Susan E.; Jimenez, Elvira E.; Chu, Karen; Atkins, David; Denietolis, Angela; Asch, Steven M.; ,
Abstract: Objective: The Veterans Health Administration (VHA) conducted a randomized quality improvement evaluation to determine whether augmenting patient‐centered medical homes with Primary care Intensive Management (PIM) decreased utilization of acute care and health care costs among patients at high risk for hospitalization. PIM was cost‐neutral in the first year; we analyzed changes in utilization and costs in the second year. Data sources: VHA administrative data for five demonstration sites from August 2013 to March 2019. Data sources: Administrative data extracted from VHA's Corporate Data Warehouse. Study design: Veterans with a risk of 90‐day hospitalization in the top 10th percentile and recent hospitalization or emergency department (ED) visit were randomly assigned to usual primary care vs primary care augmented by PIM. PIM included interdisciplinary teams, comprehensive patient assessment, intensive case management, and care coordination services. We compared the change in mean VHA inpatient and outpatient utilization and costs (including PIM expenses) per patient for the 12‐month period before randomization and 13‐24 months after randomization for PIM vs usual care using difference‐in‐differences. Principal findings: Both PIM patients (n = 1902) and usual care patients (n = 1882) had a mean of 5.6 chronic conditions. PIM patients had a greater number of primary care visits compared to those in usual care (mean 4.6 visits/patient/year vs 3.7 visits/patient/year, p < 0.05), but ED visits ( p = 0.45) and hospitalizations ( p = 0.95) were not significantly different. We found a small relative increase in outpatient costs among PIM patients compared to those in usual care (mean difference + 928/patient/year, p = 0.053), but no significant differences in mean inpatient costs (+245/patient/year, p = 0.97). Total mean health care costs were similar between the two groups during the second year (mean difference + 1479/patient/year, p = 0.73). Conclusions: Approaches that target patients solely based on the high risk of hospitalization are unlikely to reduce acute care use or total costs in VHA, which already offers patient‐centered medical homes.